2023
DOI: 10.1002/anie.202302198
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Single Molecular Channel Showing High Chloride Transport Selectivity and pH‐Responsive Conductance

Abstract: Inspired by the unique structure and function of the natural chloride channel (ClC) selectivity filter, we present herein the design of a ClC-type single channel molecule. This channel displays high ion transport activity with half-maximal effective concentration, EC 50 , of 0.10 μM, or 0.075 mol % (channel molecule to lipid ratio), as determined by fluorescent analysis using lucigenin-encapsulated vesicles. Planar bilayer lipid membrane conductance measurements indicated an excellent Cl À /K + selectivity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Although trapezoids are widely present in nature and science, to the best of our knowledge, this is the first trapezoidal benzene cage. Afterwards, taking the anion (as tetrabutylammonium salts) recognition 45–53 characteristics of 1 as an example, we demonstrated one aspect of the properties of the trapezoidal cage.…”
Section: Introductionmentioning
confidence: 95%
“…Although trapezoids are widely present in nature and science, to the best of our knowledge, this is the first trapezoidal benzene cage. Afterwards, taking the anion (as tetrabutylammonium salts) recognition 45–53 characteristics of 1 as an example, we demonstrated one aspect of the properties of the trapezoidal cage.…”
Section: Introductionmentioning
confidence: 95%
“…Similar to natural ion channels, 155 the selectivity of synthetic channels is highly dependent on both the pore lumen size and the type of functional groups in the pore lumen. Starting from several ground-breaking works in 1990s, 156–158 synthetic channels that can selectively transport K + , 159 Cl − , 160 I − , 161 and H 2 O 162 have been reported. Currently, efforts are focusing on constructing channels that can selectively transport smaller cations.…”
Section: Sensors Of Molecular Robotsmentioning
confidence: 99%
“…With the development of advanced characterization techniques, the complex structures of natural sodium channels have gradually been resolved, of which the selectivity filters determine the ion selectivity for sodium ions. In fact, the selective filter structures of natural sodium channels exhibit significant diversity within different physiological environments, and thus display distinct Na + /K + ion selectivity ( P Na/K ) ratios ranging from 12 to 50. The complex structure and utilization difficulties of natural sodium channels severely restrict their applications in life systems, and the manufacture of artificial channels with concise structures and excellent performance will provide an alternative approach to compensate for functional deficiencies of natural ion channels. As the counterpart of intracellular sodium ions, artificial channels that selectively transport K + , such as supramolecular, unimolecular, and even carriers have been widely explored. For instance, biomimetic potassium channels based on helical foldamers with ion selectivity of up to P Na/K = 32 have been developed by us recently . Moreover, we found that the lumen size of 2.5 Å is the critical size for the transformation of ion selectivity between potassium and sodium ions .…”
Section: Introductionmentioning
confidence: 99%